2011
DOI: 10.1007/s11160-011-9206-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and welfare of aquatic animals in wild capture fisheries

Abstract: The expansion of commercial aquaculture production has raised awareness of issues relating to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 184 publications
(320 reference statements)
0
47
0
Order By: Relevance
“…Davis 2002, Cooke et al 2013b) and reflex (e.g. Davis 2010) endpoints serve as objective indicators of animal welfare in fisheries (Diggles et al 2011, Cooke et al 2013b) and can be used to inform conservation actions (Wikelski & Cooke 2006, Seebacher & Franklin 2012 given their utility in defining cause and effect relationships and elucidating mechanisms of mortality (Cooke & O'Connor 2010, Cooke et al 2013a. By determining how species respond to forced submergence associated with incidental capture, we can assist managers in the development of successful and sustainable bycatch reduction strategies.…”
Section: A P (C O N T R O L) M a P (T R E A T M E N T ) M A Le (C Omentioning
confidence: 99%
See 1 more Smart Citation
“…Davis 2002, Cooke et al 2013b) and reflex (e.g. Davis 2010) endpoints serve as objective indicators of animal welfare in fisheries (Diggles et al 2011, Cooke et al 2013b) and can be used to inform conservation actions (Wikelski & Cooke 2006, Seebacher & Franklin 2012 given their utility in defining cause and effect relationships and elucidating mechanisms of mortality (Cooke & O'Connor 2010, Cooke et al 2013a. By determining how species respond to forced submergence associated with incidental capture, we can assist managers in the development of successful and sustainable bycatch reduction strategies.…”
Section: A P (C O N T R O L) M a P (T R E A T M E N T ) M A Le (C Omentioning
confidence: 99%
“…Given that most endangered species legislations extend beyond mortality to include sublethal disturbances (e.g. 'harm' and 'harassment' are forbidden by the Canadian Species at Risk Act), efforts to document physiological and behavioural impairments could provide an objective means of evaluating consequences of different types of fisheries activities while also providing information on animal welfare (Diggles et al 2011 …”
Section: A P (C O N T R O L) M a P (T R E A T M E N T ) M A Le (C Omentioning
confidence: 99%
“…Conservation initiatives arising from biotelemetry-based research could require buy-in from First 08p5 Nations groups to succeed, especially if changes to fishing practices are involved. Of interest in this study was the fact that the stakeholders had such concern for the welfare of tagged fish (Diggles et al, 2011), which emphasizes the need to ensure that tagging techniques are validated and done in a manner that maintains the welfare status of tagged fish. This perspective is in line with that of the research team because maximizing fish welfare is conducive to minimizing handling/tagging effects, an inherent objective of any tagging study .…”
Section: Mots-clésmentioning
confidence: 99%
“…Concerns about the welfare of production animals have extended from farm animals to fish in aquaculture and capture fisheries (Diggles et al, 2011, Huntingford et al, 2006. Huntingford et al (2006) reviewed the scientific literature on fish welfare and identified welfare issues that arise in aquaculture, recreational fisheries and ornamental fish keeping, but they did not identify the welfare issues that arise in capture fisheries other than pointing out that "there is very little information on the welfare of fish in the context of commercial fisheries" (Huntingford et al, 2006: 362).…”
Section: Introductionmentioning
confidence: 99%
“…Ashley et al, 2006, Sneddon et al, 2003, there is still debate whether or not fish can consciously experience noxious stimuli. Chandroo et al (2004b), Huntingford et al (2006) and Braithwaite (2010), among others, advocate a focus on the welfare of individual fish based on the perspective that fish can consciously experience noxious stimuli, whereas Diggles et al (2011), Rose et al (2014) and Key (2014), among others, dismiss this perspective and advocate a focus on fish welfare from a population perspective, aimed at reducing mortality (which relates to fish welfare) due to fishing (Diggles et al, 2011, Rose et al, 2014. Despite the debate whether or not fish can consciously experience noxious stimuli, fish welfare is increasingly acknowledged to be an important issue (Arlinghaus et al, 2007, Braithwaite and Boulcott, 2008, Branson, 2008.…”
Section: Introductionmentioning
confidence: 99%